(Metallo)porphyrins for potential materials science applications - Smykalla, Lars; Mende, Carola; Fronk, Michael; Siles, Pablo F; Hietschold, Michael; Salvan, Georgeta; Zahn, Dietrich R T; Schmidt, Oliver G; Rüffer, Tobias; Lang, Heinrich (Beilstein journal of nanotechnology, 2017)
The bottom-up approach to replace existing devices by molecular-based systems is a subject that attracts permanently increasing interest. Molecular-based devices offer not only to miniaturize the device further, but also to benefit from advanced functionalities of deposited molecules. Furthermore, the molecules itself can be tailored to allow via their self-assembly the potential fabrication of devices with an application potential, which is still unforeseeable at this time. Herein, we review efforts to use discrete (metallo)porphyrins for the formation of (sub)monolayers by surface-confined polymerization, of monolayers formed by supramolecular recognition and of thin films formed by sublimation techniques. Selected physical properties of these systems are reported as well. The application potential of those ensembles of (metallo)porphyrins in materials science is discussed.